Vanadium oxide - poly(3,4-ethylenedioxythiophene) cathodes for zinc-ion batteries: effect of synthesis temperature - Filipp S. Volkov; Svetlana N. Eliseeva; Mikhail A. Kamenskii; Alexey I. Volkov; Elena G. Tolstopjatova; Veniamin V. Kondratiev (Journal of Electrochemical Science and Engineering, 2023)
Vanadium oxide composites with conducting polymer poly(3,4-ethylenedioxythiophene) (PEDOT) were obtained by one-step microwave-assisted hydrothermal synthesis at two different temperatures: 120 and 170 °C (denoted as V-120 and V-170, respectively). The structure and composition of the obtained samples were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) analysis, X-ray photoelectron spectroscopy (XPS), and thermogravimetric (TG) analysis. The detailed study of the electrochemical properties of the composites as cathodes of aqueous zinc-ion battery was performed by cyclic voltammetry (CV), galvanostatic charge-discharge (GCD) at different current densities and by electrochemical impedance spectroscopy (EIS). It was shown that V-120 demonstrated excellent electrochemical performance in the 0.3 to 1.4 V vs. Zn/Zn2+ potential range reaching specific capacities of up to 390 mA∙h∙g−1 at 0.3 A∙g−1 with excellent capacity stability after 1000 charge-discharge cycles. Its functional parameters were found to be much better than those of the electrodes based on the V-170 composite obtained at a higher temperature. The effect of the synthesis temperature on the electrochemical properties is discussed in terms of the crystallographic, compositional, and thermogravimetric properties of the samples.